PP.42.02: CONTRIBUTION OF A GENETIC SCORE IN THE RISK ASSESSMENT OF ARTERIAL HYPERTENSION. (June 2015) - Sousa, A.C.; Reis, R. Palma Dos; Pereira, A.; Gomes, S.; Rodrigues, R.; Ferreira, R.; Freitas, A.I.; Guerra, G.; Freitas, S.; Rodrigues, M.; Freitas, C.; Ornelas, I.; et al.
Abstract : Objective: Arterial hypertension (AHT) is a multifactorial disease in which the genetic contribution is particularly important. It is estimated that about 30% of the blood pressure values are genetically determined. Multiple genes have been associated to AHT, but sometimes without statistical significance. Create a score with genes pathophysiologically associated with AHT determine the risk of developing this disease. Design and method: Case-control study which included 1063 individuals, 487 patients with AHT (mean age 51.8 ± 7.6; 48.7% male) and 576 controls (mean age 51.1 ± 7.4; 46.5% male). We selected 12 gene variants associated with hypertension namely, those of the Renin Angiotensin Aldosterone System (AGT 174 M/T; AGT 235 T/M; ACE I/D; ACE 8 A/G; AT1R 1166 A/C; CYP11B2 -344 C/T, CYP17A1 T/C); the balance of sodium and water (SNN1G A -173 G, ADD1 Gly460Trp); the sympathetic adrenergic system (β1 Adrenergic R389G, β2 adrenergic R16G); and other candidate genes as ATP2 B1 A/G and the Sub Unit β3 Protein G C825T. The odds ratio (OR) for each of the genetic variants was calculated and the multiplicative score was then determined based on the risk multiplication (OR) of each genotype of the 12 studied variants. This score was divided into tertiles, considering the 1st tertile of OR as the reference class and compared with the 3rd tertile in terms of AHT development. Results: The genetic score generated by using 12 genetic polymorphisms presented an AHT risk of 2.07 (CI: 1.53 to 2.80; p < 0.0001), comparing the 3rd tertile with the 1st tertile (Table). Figure. No caption available. Conclusions: These results show that a genetic score, based on the multiplicative effect of a number of risk genotypes, in some genetic markers was associated with an increased AHT risk. This score can be very useful in predicting the development of hypertension in the general population. Thus, hypertension results of a cumulative process of several risk genes and also habits and behaviors that facilitate the disease onset.